Demarcating Deification and the Indwelling of the Holy Spirit in Reformed Theology - Leidenhag Joanna (Perichoresis: The Theological Journal of Emanuel University, 2020)
The recent interest in exploring whether authoritative figures of the Reformed tradition employed a concept of theōsis or deification in their soteriology continues to grow. However, it is yet unclear how the supposed implicit Reformed doctrine of deification relates to the more explicit concept of the indwelling of the Holy Spirit. Moreover, many of the arguments for theōsis in the theology of John Calvin, Jonathan Edwards, or T. F. Torrance seem to rely on confusing these two soteriological concepts. This makes it almost impossible to assess if it is theōsis or the indwelling of the Holy Spirit (or some interesting combination) that is being appealed to in Reformed thinking. This paper makes a step towards unpicking the knot between the indwelling of the Holy Spirit and theōsis in Reformed theology by offering five possible ways to demarcate these two concepts. It is concluded that the final ‘Mereological Demarcation’ is currently the most acceptable.